Manufacture, electromagnetic properties and microstructure of an 18-filament jelly-roll Nb3Al superconducting wire with rapid heating and quenching heat-treatment. (1st December 2015) - Pan, X F; Feng, Y; Yan, G; Cui, L J; Chen, C; Zhang, Y; Wu, Z X; Liu, X H; Zhang, P X; Bai, Z M; Zhao, Y; Li, L F
Abstract: In this paper, we have reported the manufacture of a novel simple-structured jelly-roll Nb3 Al precursor long wire, and its electromagnetic properties and microstructure with different rapid heating and quenching (RHQ) heat-treatments. By comparing three processing methods, it is found that the rolling and drawing (RD) method is more suitable to the fabrication of kilometer-length Nb3 Al precursor wire without annealing. Using homemade RHQ equipment, we have successfully carried out RHQ heat-treatment of Nb3 Al wire samples with various heating conditions. Based on magnetization and magnetoresistivity measurements, the onset superconducting transition temperature, T c and upper critical field, H c2 (0) of optimal Nb3 Al wire reach 17.9 K–18.0 K and 29.7 T, respectively. Through microstructure and composition analysis, the Nb3 Al superconductor in the optimal wire displays a typical 'layer-to-layer' structure, which comprises alternate crystalline Nb3 Al and amorphous Nb layers, and the Nb3 Al grains sizes are about 100 nm–300 nm. Furthermore, many small holes are dispersed in the Nb3 Al superconductor due to the diffusion reaction from Al to Nb site. The work suggests the simple-structured Nb3 Al precursor wire with RHQ heat-treatment is very promising for high-field application.